2013
DOI: 10.1071/wf12215
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire response variability in Mediterranean Basin tree species in Portugal

Abstract: Fire is the most important natural disturbance driving vegetation dynamics in the Mediterranean Basin. However, studies relating fire-induced tree responses to both fire severity and plant traits are still scarce in this region. We aimed to investigate such relationships further and to develop simple models that could help improve forest management in these fire-prone ecosystems. We compiled data from 16 fire sites in different regions and used models to relate post-fire responses of 4155 trees from 14 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Other studies have observed this discrepancy between actual mortality and top-kill (e.g. Catry et al 2013), although most mortality models are primarily focussed on top-kill. This result underscores the need to develop more species-specific models for FOFEM, and the need to consider multiple types of mortality for hardwoods.…”
Section: Model Validationmentioning
confidence: 94%
“…Other studies have observed this discrepancy between actual mortality and top-kill (e.g. Catry et al 2013), although most mortality models are primarily focussed on top-kill. This result underscores the need to develop more species-specific models for FOFEM, and the need to consider multiple types of mortality for hardwoods.…”
Section: Model Validationmentioning
confidence: 94%
“…In general, Pinus species in the Iberian Peninsula's forests are obligated seeders whose post-fire regeneration relies on seeds stored in serotinous cones within the canopy level (Calvo et al, 2008(Calvo et al, , 2016. However, this natural regeneration could fail due to severe wildfires, as regeneration from aerial seed banks could be hindered (Calvo et al, 2008;Catry et al, 2013). Depending on burn severity, fire not only affects the regeneration of dominant tree species but also the understory community.…”
Section: Introductionmentioning
confidence: 99%
“…FireFreq was particularly relevant in hampering the regeneration of temperate sub-Mediterranean taxa (Q. robur and Q. pyrenaica). Although Quercus species resprout after fire [114], frequent fires can exhaust belowground storage reserves precluding further resprouting and kill saplings that have not yet stored enough reserves for resprouting [115].…”
Section: Discussionmentioning
confidence: 99%